Evaluation of an inkless method for fingerprint recordings using hand sanitizer gel on thermal paper. (June 2021) - De Alcaraz-Fossoul, Josep; Li, Sihai
Highlights: An inkless method to obtain exemplar fingerprints is evaluated using two quality assessment systems. ULW metrics have proven more sensitive and reliable than QS quality scores. Differences in qualities are attributed to deposition method, biological sex, and examiner effects. The proposed inkless method performs similarly to the conventional inked technique. A quality metric assessment for fingerprint-based research would be beneficial to standardize examinations. Abstract: The main objective of this project was to assess an inkless method to collect reference (exemplar) fingerprints as a low-cost, portable, and hygienic technique; for temporary storage and as an alternative to the conventional black ink method. The tested inkless approach requires alcohol-based hand sanitizer gel as the medium and thermal paper as the substrate. The final quality and clarity of fingerprints were examined and compared between the two methods, especially on the basis of medium/substrate and biological sex effects. Two different evaluation systems of visual quality (clarity) were conducted to provide more reliable results: a quality score scheme (QS) and metrics from the FBI's Universal Latent Workstation (ULW). Fingerprints were obtained from 20 individuals (11 males and 9 females) between the ages of 20 and 40; a total of 240 impressions were evaluated. The results provide evidence that the inkless method produces identifiable fingerprints of equivalent quality to the standard ink method, although significantly better for males. The potential of the proposed technique as an alternative to the conventional ink method is proven and corroborated by the two independent systems of visual quality assessments.